Risk of immune‐related pneumonitis for PD1/PD‐L1 inhibitors: Systematic review and network meta‐analysis - Yafang Huang; Haiyu Fan; Ning Li; Juan Du (Cancer Medicine, 2019)
Abstract Background Immune‐related pneumonitis is a clinically relevant and potentially life‐threatening adverse event. We performed a systematic review and network meta‐analysis to compare the risk of immune‐related pneumonitis among different PD1/PD‐L1 inhibitor‐related therapeutic regimens. Methods Randomized controlled trials with PD1/PD‐L1 inhibitors were identified through comprehensive searches of multiple databases. Both published and unpublished data were extracted. Bayesian NMA was performed using random‐effects models. All‐grade (Grade 1‐5) and high‐grade (Grade 3‐5) immune‐related pneumonitis were estimated using odds ratios (ORs). Results A total of 25 studies involving 16 005 patients were included. Compared with chemotherapy, the ORs of immune‐related all‐grade and high‐grade pneumonitis were significant for nivolumab (all‐grade: OR = 6.29, 95% CrI: 2.67‐16.75; high‐grade: OR = 5.95, 95% CrI: 2.35‐17.29), pembrolizumab (all‐grade: OR = 5.78, 95% CrI: 2.79‐13.24; high‐grade: OR = 5.33, 95% CrI: 2.49‐12.97), and nivolumab plus ipilimumab therapy (all‐grade: OR = 14.82, 95% CrI: 5.48‐47.97; high‐grade: OR = 15.26, 95% CrI: 5.05‐55.52). Compared with nivolumab, nivolumab plus ipilimumab therapy was associated with an increased risk of all‐grade pneumonitis (OR = 2.34, 95% CrI: 1.07‐5.77). Nivolumab plus ipilimumab therapy had the highest risk of both all‐grade and high‐grade pneumonitis among PD1/PD‐L1 inhibitor‐related therapeutic regimens. Conclusions This study demonstrates that compared with chemotherapy, PD‐1 inhibitor may result in a higher risk of immune‐related pneumonitis. Nivolumab plus ipilimumab therapy had the highest pneumonitis risk. These findings could be taken into account by the physicians in decision making.